Teaching accounting principles using augmented reality and artificial intelligence-generated IsiZulu language translations - Abejide Ade-Ibijola; Aneetha Sukhari; Solomon Sunday Oyelere (International Journal of Educational Research Open, 2025)
One of the sustainable development goals identified by the United Nations (UN) aims to ensure inclusive, equitable, quality education and promote lifelong learning opportunities for all. The report issued by the UN in 2022 highlighted that the global education crisis for vulnerable groups has worsened due to the COVID-19 pandemic, war, lack of infrastructure, and little or no psychosocial support. The prevalence of English as the medium of instruction in higher education, is a challenge for students who speak English as a second language. In South Africa, and Africa as a whole, the majority of the population speak in their mother tongue as a first language, which is problematic for students enrolled at English medium universities. This study focuses on accounting education from a South African perspective. Earlier research found that the number of African chartered accountants in South Africa are inadequately represented and cited one of the reasons as being a language barrier. We propose that the translation of accounting concepts into indigenous African languages can improve the understanding of accounting principles which will allow for inclusive, equitable, and quality education for all. In doing so, we develop a prototype application, which encompasses augmented reality and artificial intelligence-generated language translation functionalities to teach accounting principles in an indigenous African language, namely, IsiZulu. The application, named Zulu Augmented Reality Translation (ZART), aids the learning process of accounting principles, by providing an engaging and interactive learning experience in IsiZulu. The paper commences with a literature review on the teaching pedagogy and challenges in accounting education. Thereafter, the design science research applied in the development of ZART is discussed. Using questionnaires, an experiment is conducted to evaluate the usability of ZART, students’ perceptions and pedagogical experiences of using ZART. The results of the evaluation show that ZART was easy to install and use; students were captivated with the avatars in ZART; and the language translation functionality was useful for learning the basics of accounting. ZART is of importance to policy makers and standard setters in the accounting profession, accounting academics, and accounting students. This study provides a platform for the translation of the accounting curriculum into numerous indigenous African languages.